ANALISIS PROFITABILITAS USAHA PENGOLAHAN KEDELAI PADA IRT TASIK GARUT DI KABUPATEN LEBONG - Reswita, Reswita (Jurnal AGRISEP, 2013)
This research is aimed to estimate income and profitability of the soybean processing business in District of Lebong. The study is case study on Tasik Garut Home Industry. Two profitability methods are used to analyse data obtained, i.e., business income and Net Profit Margin. Results of research showed that business income is Rp. 30,682,083 per month or Rp. 1,022, 736.111 dayly and Profit Margin of 48.6%.